Culturing Security System of Chemical Laboratory in Indonesia - Eka Dian Pusfitasari (Indonesian Journal of Chemistry, 2017)
Indonesia has experiences on the lack of chemical security such as: a number of bombing terrors and hazardous chemicals found in food. Bomb used in terror is a homemade bomb made from chemicals which are widely spread in the research laboratories such as a mixture of pottasium chlorate, sulphur, and alumunium. Therefore, security of chemicals should be implemented to avoid the misused of the chemicals. Although it has experienced many cases of the misuse of chemicals, and many regulations and seminars related to chemical security have been held, but the implementation of chemical security is still a new thing for Indonesian citizens. The evident is coming from the interviews conducted in this study. Questions asked in this interview/survey included: the implementation of chemical safety and chemical security in laboratory; chemical inventory system and its regulation; and training needed for chemical security implementation. Respondents were basically a researcher from Government Research Institutes, University laboratories, senior high school laboratories, and service laboratories were still ambiguous in distinguishing chemical safety and chemical security. Because of this condition, most Indonesia chemical laboratories did not totally apply chemical security system. Education is very important step to raise people awareness and address this problem. Law and regulations should be sustained by all laboratory personnel activities to avoid chemical diversion to be used for harming people and environment. The Indonesia Government could also develop practical guidelines and standards to be applied to all chemical laboratories in Indonesia. These acts can help Government’s efforts to promote chemical security best practices which usually conducted by doing seminars and workshop.